Postprandial symptoms originating from the stomach in functional dyspepsia. Issue 11 (2nd September 2013) - Vanheel, H.; Vanuytsel, T.; Van, L.; Farré, R.; Verbeke, K.; Tack, J.
Abstract Background Functional dyspepsia (FD) is characterized by chronic epigastric symptoms. The stomach has been held responsible for the generation of symptoms, but the latest reports have pointed out that also the duodenum can be implicated in the pathophysiology. The aim of this study was to elucidate which dyspeptic symptoms originate from the stomach and/or from the small intestine after a meal. Methods Two hundred eighty‐four FD patients underwent a gastric emptying breath test. Breath samples were taken and the intensity of six dyspeptic symptoms (fullness, bloating, belching, nausea, epigastric burning, and epigastric pain) was scored before a meal and at 15 min intervals for a period of 240 min postprandially. Time curves of each symptom were analyzed and severity scores during the gastric and the intestinal phase were compared. Key Results Time curves of fullness, bloating, belching, and nausea displayed a significant negative slope, while symptom severity of epigastric burning and epigastric pain did not decrease over time. Numerical analysis revealed that scores for fullness, bloating, and belching were higher during the gastric phase compared with the intestinal phase. On the other hand, intensities of nausea, epigastric burning, and epigastric pain were similar during both phases. Conclusions & Inferences Intensities of fullness, bloating, and belching decrease with food moving from the stomach to the small intestine indicating that the stomach plays a crucial role in the generation of these symptoms. In contrast, the symptom severity of epigastric burning and epigastric pain persists with progression of food to the small intestine.